CSF Biomarkers of Neurodegeneration in Progressive Non-fluent Aphasia and Other Forms of Frontotemporal Dementia: Clues for Pathomechanisms? - Körtvelyessy, Peter; Heinze, Hans J.; Prudlo, Johannes; Bittner, Daniel (Frontiers in Neurology, 2018)
Frontotemporal Dementia (FTD) encompasses distinct pathophysiologically heterogenous disorders with different genetic and cellular disease mechanisms. The objective of this study is to compare the constellation of biomarkers of neurodegeneration in the cerebrospinal fluid (CSF) to the FTD type categorized by clinical symptoms. We investigated the levels of Phospho181-tau, Total-tau, Beta-amyloid1-42, Neurofilament light chain and Progranulin in the CSF of n=99 FTD patients regarding to the different subtypes of FTD, including semantic dementia (SD), progressive non-fluent aphasia (PNFA), behavioural variant FTD (bvFTD). We compared these groups to patients without neurodegenerative disorders and another cohort encompassing tauopathies with distinct clinical syndromes (Cortico basal syndrome and progressive supranuclear palsy) and logopenic PNFA (lPPA) as another disorder with predominant speech disturbance.. CSF-Progranulin levels were significantly lower in FTD type patients with semantic dementia and behavioral variant FTD mainly attributed to the Tar-DNA-Binding-Protein (TDP) 43 compared to predominantly Tau-mediated PNFA (p<0.05). Also, neurofilament light chain was significantly higher (p<0.036) in all FTD patients especially in SD patients (p<0.01). CSF-Nfl levels also distinguished SD patients from logopenic Alzheimers patients (p<.05). In sum, CSF-Neurofilament light chain and CSF-Progranulin seem to be promising biomarkers for FTD, the latter predominantly for assumed TDP43-mediated FTD.